Introduction of the Personnel Decision Support IT System in the Hungarian Public Service - Hazafi, Zoltán; Kovácsné Szekér , Enikő (Public Governance, Administration and Finances Law Review, 2022)
The most significant project of governmental HRM after 2010 has been the “Strategic Support for Succession Planning in a Competitive Civil Service”. The name of the project underlines the focus placed on enhancing competitiveness and ensuring a sustainable, continuous supply of the workforce. Neither can be pursued without data-driven HR planning, so having an HRM decision support system in place is a critical element of the improvement. This study aims to address the issue of optimal headcount with regard to both domestic and foreign context, emphasise the importance of strategic HR planning and explore its results abroad. It suggests that by establishing the new HRM system, Hungary may become a country at the forefront of public service HRM and digitalisation.